Corrigendum to “sulfated hyaluronic acid/collagen-based biomimetic hybrid nanofiber skin for diabetic wound healing: Development and preliminary evaluation” [carbohydrate polymers, volume 334, 15 June 2024, 122025] - Yuanmeng Zhou; Weibin Jia; Jiexue Bi; Meng Liu; Liling Liu; Hang Zhou; Guofeng Gu; Zonggang Chen (Carbohydrate Polymers, 2026)

pH stability improved electrochemical biosensor based on dopamine/aptamer imprinted polymer modified electrodes for simultaneous detection of four toxic metal ions - Jiahao Sha; Liling Hao; Xinyu Fang; Nianxin Zhu; Yihang Yang; Kaiming Peng; Tai Ye; Hui Cao; Huajie Gu; Fei Xu (Food Control, 2025)

Sulfated hyaluronic acid/collagen-based biomimetic hybrid nanofiber skin for diabetic wound healing: Development and preliminary evaluation - Yuanmeng Zhou; Weibin Jia; Jiexue Bi; Meng Liu; Liling Liu; Hang Zhou; Guofeng Gu; Zonggang Chen (Carbohydrate Polymers, 2024)

NLRC3 attenuates osteoclastogenesis by limiting TNFα+ Th17 cell response in osteoporosis - Lingyan Ren; Guangjun Liu; Yun Bai; Liling Gu; Yuan Wang; Li Sun (Journal of Molecular Medicine, 2024)
NOD-like receptor family CARD domain containing 3 (NLRC3) is the intracellular protein belonging to NLR (NOD-like receptor) family. NLRC3 can negatively regulate inflammatory signal transduction pathways within the adaptive and innate immunocytes. However, studies need to elucidate the biological role of NLRC3 in bone remodeling. Herein, our study proved that NLRC3 prevents bone loss by inhibiting TNFα + Th17 cell responses. In osteoporosis, NLRC3 attenuated TNFα + Th17 cell accumulation in the bone marrow. However, osteoporosis (OP) development was aggravated without affecting bone marrow macrophage (BMM) osteoclastogenesis in NLRC3-deficient ovariectomized (OVX) mice. In this study, we transferred the wild-type and NLRC3 −/− CD4 + cells into Rag1 −/− mice. Consequently, we evidenced the effects of NLRC3 in CD4 + T cells on inhibiting the accumulation of TNFα + Th17 cells, thus restricting bone loss in the OVX mice. Simultaneously, NLRC3 −/− CD4 + T cells promoted the recruitment of osteoclast precursors and inflammatory monocytes into the OVX mouse bone marrow. Mechanism-wise, NLRC3 reduced the secretion of TNFα + Th17 cells of RANKL, MIP1α, and MCP1, depending on the T cells. In addition, NLRC3 negatively regulated the Th17 osteoclastogenesis promoting functions via limiting the NF-κB activation. Collectively, this study appreciated the effect of NLRC3 on modulating bone mass via adaptive immunity depending on CD4 + cells. According to findings of this study, NLRC3 may be the candidate anti-OP therapeutic target. Key messages NLRC3 negatively regulated the Th17 osteoclastogenesis promoting functions via limiting the NF-κB activation. NLRC3 may be the candidate anti-OP therapeutic target.

Genetic and biological characteristics of the globally circulating H5N8 avian influenza viruses and the protective efficacy offered by the poultry vaccine currently used in China - Pengfei Cui; Xianying Zeng; Xuyong Li; Yanbing Li; Jianzhong Shi; Conghui Zhao; Zhiyuan Qu; Yanwen Wang; Jing Guo; Wenli Gu; Qi Ma; Yuancheng Zhang; et al. (Science China Life Sciences, 2022)
The H5N8 avian influenza viruses have been widely circulating in wild birds and are responsible for the loss of over 33 million domestic poultry in Europe, Russia, Middle East, and Asia since January 2020. To monitor the invasion and spread of the H5N8 virus in China, we performed active surveillance by analyzing 317 wild bird samples and swab samples collected from 41,172 poultry all over the country. We isolated 22 H5N8 viruses from wild birds and 14 H5N8 viruses from waterfowls. Genetic analysis indicated that the 36 viruses formed two different genotypes: one genotype viruses were widely detected from different wild birds and domestic waterfowls; the other genotype was isolated from a whopper swan. We further revealed the origin and spatiotemporal spread of these two distinct H5N8 virus genotypes in 2020 and 2021. Animal studies indicated that the H5N8 isolates are highly pathogenic to chickens, mildly pathogenic in ducks, but have distinct pathotypes in mice. Moreover, we found that vaccinated poultry in China could be completely protected against H5N8 virus challenge. Given that the H5N8 viruses are likely to continue to spread in wild birds, vaccination of poultry is highly recommended in high-risk countries to prevent H5N8 avian influenza.

Transcriptome profiling provides insights into the fruit color development of wild Lycium ruthenicum Murr. from Qinghai–Tibet Plateau - Yinyan Qi; Haibin Wei; Wenyi Gu; Wenjun Shi; Liling Jiang; Lei Deng; Xiaoli Liu (Protoplasma, 2021)

Glycosylation and an amino acid insertion in the head of hemagglutinin independently affect the antigenic properties of H5N1 avian influenza viruses - Chunyang Gu; Xianying Zeng; Yangming Song; Yanbing Li; Liling Liu; Yoshihiro Kawaoka; Dongming Zhao; Hualan Chen (Science China Life Sciences, 2019)